I farmaci “generici” in Italia: opportunità di ricerca e sviluppo di prodotti di qualità a prezzi competitivi - Eandi, Mario; Della Pepa, Carlo (Farmeconomia. Health economics and therapeutic pathways, 2003)
Every drug whose copyright coverage has expired can be manufactured by a pharmaceutical company other than the one that developed it, giving rise to the market of the so-called generic drugs. It can be distinguished among two types of generic drugs: branded and unbranded, according to the choice of the manufacturer to assign it a fantasy name or to sell it with the name of the active principle, followed by the company’s name. In order to be accepted for marketing, every new drug has to pass the registration procedures of the Italian Ministry of Health, which are simplified for generics, as it’s sufficient to demonstrate the bioequivalence, considered a reliable proxy of therapeutic equivalence, of the new drug with the standard formulations it copies. The bioequivalence of two drugs depends on various parameters, related to the quality of the raw materials employed and the industrial processes they go through. There are several ways of assessing the equivalence between pharmaceutical products, and it is important the registration studies are conducted following strict rules, in order to guarantee the quality of generics, fundamental for achieving the trust of health operators and patients. The reason to be of generic drugs is essentially economic, as they bare no therapeutic innovation, and their introduction is mainly aimed to contain drug expenditures and to facilitate a competitive market, but to do so, they need to be widely accepted by the medical community and the population. In Italy, the market of generic drugs is very young and relatively underdeveloped if compared to what is observed in other industrialized countries such as the USA, Germany or UK, but it has a good expansion potential, as it also represents a chance for quality enhancement for the Italian pharmaceutical industry.